2016
DOI: 10.2147/ijn.s104856
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of synaptic plasticity by fullerenol in rat hippocampus in vitro

Abstract: Fullerenol, a water-soluble fullerene derivative, has attracted much attention due to its bioactive properties, including the antioxidative properties and free radical scavenging ability. Due to its superior nature, fullerenol represents a promising diagnostic, therapeutic, and protective agent. Therefore, elucidation of the possible side effects of fullerenol is important in determining its potential role. In the present study, we investigated the acute effects of 5 μM fullerenol on synaptic plasticity in hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…A recent article has shown that fullerenols have neuroprotective activities, including promoting restoration of dopamine levels, reducing oxidative stress, preventing death of neurons and alleviating aggregation of alpha-synuclein [ 34 ]. But our previous study of fullerenol on synaptic plasticity in hippocampal brain slices of rats indicates that high-level fullerenols depress the activity and the expression of nitric oxide synthase in hippocampus [ 35 ]. The role of fullerenols in the nervous system is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…A recent article has shown that fullerenols have neuroprotective activities, including promoting restoration of dopamine levels, reducing oxidative stress, preventing death of neurons and alleviating aggregation of alpha-synuclein [ 34 ]. But our previous study of fullerenol on synaptic plasticity in hippocampal brain slices of rats indicates that high-level fullerenols depress the activity and the expression of nitric oxide synthase in hippocampus [ 35 ]. The role of fullerenols in the nervous system is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…CaMKII, an enzyme primarily in the brain, belonging to the calcium-activated serine/threonine protein kinase family, is a key protein downstream of the NMDA receptor signaling pathway, and a core protein in the calcium ion signaling pathway is also involved in the synthesis and release of glutamate, the regulation of ion channels, and the regulation of synaptic retractions . Moreover, CaMKII has a long-lasting enzymatic activity for LTP regulation and is therefore considered to be a molecular switch . The presence of the Ca signaling pathway is an integral part of the normal function of synaptic maintenance in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…55 Moreover, CaMKII has a long-lasting enzymatic activity for LTP regulation and is therefore considered to be a molecular switch. 56 The presence of the Ca signaling pathway is an integral part of the normal function of synaptic maintenance in the hippocampus. The transfer of neurotransmitter to the postsynaptic membrane is accompanied by the influx of Ca2+ into the membrane through NMDAR, which in turn causes the activation of CaMKIIA 57 and the whole signaling pathway.…”
Section: Regulation Of Neural Plasticitymentioning
confidence: 99%
“…Some studies show that NO affects the hippocampal synaptic plasticity, including LTD and LTP, and consequently learning and memory [ 49 54 ]. Also, NO serves as a retrograde messenger and acts directly on the presynaptic neurons to produce LTP [ 48 , 55 57 ] and then suppresses the synaptic plasticity [ 58 ]. Other studies have shown that some drugs could protect the hippocampal neurons by inhibiting the NOS activity and expression in the hippocampus [ 58 60 ].…”
Section: Hypoxic Injury and Neuronal Plasticitymentioning
confidence: 99%
“…Also, NO serves as a retrograde messenger and acts directly on the presynaptic neurons to produce LTP [ 48 , 55 57 ] and then suppresses the synaptic plasticity [ 58 ]. Other studies have shown that some drugs could protect the hippocampal neurons by inhibiting the NOS activity and expression in the hippocampus [ 58 60 ]. The ER stress induced by chronic IH resulted in apoptosis and fine structural changes in the synapses in the hippocampal CA1 region [ 61 ], which might inhibit the transfer of Schaffer collaterals from CA3 to CA1 neurons [ 62 ].…”
Section: Hypoxic Injury and Neuronal Plasticitymentioning
confidence: 99%